Analysis of Character Education on Broken Home Students at State Elementary School 5 Dampit - Diki Puspita Sari; Toto Nusantara; Ade Eka Anggraini (SAINTIS Publishing, 2025)
This qualitative study, employing a case study design, aims to describe the implementation of character education values at SD Negeri 5 Dampit, particularly in supporting students from broken home families. Data were collected through in-depth interviews, participant observation, and documentation. The data analysis was conducted through individual case analysis and cross-case analysis to ensure comprehensive findings. The results reveal that character values, such as discipline, responsibility, empathy, and religiousness—are instilled contextually through daily school activities and integrated into the learning process both inside and outside the classroom. The holistic approach applied by teachers and school staff proves effective in fostering personal resilience and positive behavior among broken home students. As a result, the school serves as an alternative nurturing environment that significantly supports the character development of these students.